The effectiveness of ICT-supported flipped learning in an EFL context: A case of northern Iraq - Mahmood, Abubakir Muhammad; Mohammadzadeh, Behbood (Frontiers in Psychology, 2022)
Flipped Learning is a pedagogical model that leverages technology-enhanced instruction inside and outside of class time to maximize student engagement and learning during class time. This study investigated the effectiveness of ICT-supported Flipped learning in an EFL context in Northern Iraq to contribute to sustainable personalized language learning. The participants were EFL students and teachers of a primary school in Raniyah. The study employed an experimental method to collect student data and a teacher questionnaire. The results indicated that Flipped learning had statistically significant effects on the students’ academic performance and achievement. The mean scores of the post-tests scored higher than that of the pre-test. The mean scores of the EG with (M =89.15) for the fifth grade and (M =81.40) for the sixth grade were much higher than those of the CGs (M =70.40) for the fifth grade and (M =67.40) for the sixth grade which indicated that FL had a statistically great impact on the students’ academic performance and their product improvement. Besides, the results of the t-test showed a significant difference in performance between students in both EGs and CGs; the participants outstripped statistically significant on the post-test (p < 0.05) compared to the pre-test. The majority of the participants’ attitudes were positive towards Flipped learning, and they remarked that it had a significant role in learning compared to the conventional classes. The participant teachers quoted positive views on Flipped learning over traditional classes.